A serpin regulates dorsal-ventral axis formation in the Drosophila embryo. - Ligoxygakis, P.; Roth, S.; Reichhart, J.M. (Current Biology, 2003)
Extracellular serine protease cascades have evolved in vertebrates and invertebrates to mediate rapid, local reactions to physiological or pathological cues. The serine protease cascade that triggers the Toll signaling pathway in Drosophila embryogenesis shares several organizational characteristics with those involved in mammalian complement and blood clotting. One of the hallmarks of such cascades is their regulation by serine protease inhibitors (serpins). Serpins act as suicide substrates and are cleaved by their target protease, forming an essentially irreversible 1:1 complex. The biological importance of serpins is highlighted by serpin dysfunction diseases, such as thrombosis caused by a deficiency in antithrombin. Here, we describe how a serpin controls the serine protease cascade, leading to Toll pathway activation. Female flies deficient in Serpin-27A produce embryos that lack dorsal-ventral polarity and show uniform high levels of Toll signaling. Since this serpin has been recently shown to restrain an immune reaction in the blood of Drosophila, it demonstrates that proteolysis can be regulated by the same serpin in different biological contexts.